Retracted: Validation of a popular consumer-grade cuffless blood pressure device for continuous 24 h monitoring - Bhavini J Bhatt; Haashim Mohammad Amir; Siana Jones; Alexandra Jamieson; Nishi Chaturvedi; Alun Hughes; Michele Orini (European Heart Journal - Digital Health, 2025)
Abstract This article has been retracted. Please see https://doi.org/10.1093/ehjdh/ztag002 for details.